Antimicrobial activity of spices essential oils and its effectiveness on mature biofilms of human pathogens. Issue 4 (16th February 2020) - Condò, Carla; Anacarso, Immacolata; Sabia, Carla; Iseppi, Ramona; Anfelli, Igor; Forti, Luca; de Niederhäusern, Simona; Bondi, Moreno; Messi, Patrizia
Abstract: The antibacterial activity of Pimpinella anisum L., Cinnamomum zeylanicum, Syzygium aromaticum, and Cuminum cyminum L. essential oils (EOs) against some common pathogenic microorganisms ( Staphylococcus aureus ATCC 6538, Staphylococcus epidermidis ATCC 14990, Enterococcus faecalis ATCC 29212, Streptococcus pyogenes ATCC 1915, Escherichia coli ATCC 8739, Pseudomonas aeruginosa ATCC 27853, Aeromonas hydrophila ATCC 7966, Proteus mirabilis ATCC 10005, Klebsiella pneumoniae ATCC 13883, and Candida albicans ATCC 10231) and their biofilms was studied. The EOs inhibitory effects were evaluated by both Agar Well Diffusion assay and Minimum Inhibitory Concentration (MIC) determination. The most active EOs, cinnamon and cloves, were also tested on 18, 24, 48, 72 hours mature biofilms. Cinnamon and cloves exhibited the best results showing a significant activity against all the tested bacteria. Concerning biofilm, results suggest that Cinnamomum zeylanicum oil may be a useful approach to impair the biofilm produced by the tested Gram-negative bacteria. Graphical Abstract: